Development and diversification of small-scale agriculture in Afghanistan - Ahmadzai, Hayatullah (2019)
Agriculture is central to the Afghanistan’s economy. It continues to be a strategic sector in the economic development of Afghanistan in terms of its potential for contributing to household income, food security, and rural employment. The sector is dominated by resource-poor small-scale subsistence farmers emphasising food security through own production. The recent policy changes to transform the sector from a subsistence to a self-sufficient market-led system have presented opportunities but posed challenges and created uncertainties. Empirical evidence is required to assess the status of the sector, the effect of policies, and to guide future interventions. The self-contained essays in this thesis attempt to address these emerging concerns by analysing small-scale farmers production efficiency, diversification strategies, and market participation decisions.